Fluid Injection Experiments in Shale at Elevated Confining Pressures: Determination of Flaw Sizes From Mechanical Experiments. Issue 6 (21st June 2019) - Chandler, Michael R.; Mecklenburgh, Julian; Rutter, Ernest; Lee, Peter
Abstract: Triaxial experiments and direct fluid injection experiments have been conducted at confining pressures up to 100 MPa on Mancos shale, Whitby mudstone, Penrhyn slate, and Pennant sandstone. Experiments were conducted with sample axes lying both parallel and perpendicular to layering in the materials. During triaxial failure Penrhyn slate was stronger for samples with cleavage parallel to maximum principal stress, but the two orientations in the shales displayed similar failure stresses. Initial flaw sizes of around 40 μm were calculated from the triaxial data using the wing crack model, with the shales having shorter initial flaws than the nonshales. During direct fluid injection, breakdown was rapid, with no discernible gap between fracture initiation and breakdown. Breakdown pressure increased linearly with confining pressure but was less sensitive to confining pressure than expected from existing models. A fracture mechanics‐based model is proposed to determine the initial flaw size responsible for breakdown in injection experiments. Flaw sizes determined in this way agree reasonably with those determined from the triaxial data in the nonshales at low confining pressures. As confining pressure rises, a threshold is reached, above which the fluid injection experiments suggest a lower initial flaw length of around 10 μm. This threshold is interpreted as being due to the partial closure of flaws. In the shales an initial flaw length of around 10 μm was determined at all confining pressures, agreeing reasonably with those determined through the triaxial experiments. Key Points: Smaller flaws control sample failure in shales than in most other rock materials Breakdown pressure increases linearly with confining pressure in fluid injection experiments Flaws in the region of 10‐ to 40‐μm length control sample failure